System quality managment for the university extension process, an experience of the Havana’s University. (Revista Electrónica Calidad en la Educación Superior, 2020)
Quality management is a necessity and opportunity in Higher Education Institutions, to respond efficiently and effectively to the demands of society; for this reason, university processes must update their management mechanisms. The objective of this work is to develop a quality management system for the university extension process at the University of Havana, for which a concurrent mixed investigation was used. A quality management system for the extension process was obtained at the University of Havana, which consists of seven stages (Foundations, Strategic Design, Process Design, Evaluative Design, Integrated Design, Implementation and Evaluation), which is contextualized, flexible, democratic, understandable and operational. Users expressed satisfaction and recognition of the effectiveness and usefulness of the proposal once it is implemented.
Keywords: system; quality management; university extension.